Carex ×favratii (Cyperaceae), new record for Romania and evidence of its hybrid origin - Řepka, Radomír; Mendel, Peter (Phytotaxa, 2022)
The article presents a find of Carex ×favratii (Carex echinata × C. paniculata) in Romania, whose genetic relationships with its putative parents was tested using AFLP and microsatellite data. The putative hybrid was genetically intermediate between the parental taxa, i.e. C. echinata and C. paniculata. A morphological analysis shows ten intermediary characters, six ones closer to C. echinata, five closer to C. paniculata, and three unique, whereas the perigynium and achene characters could not be evaluated due to hybrid sterility (with exception of the type of perigynium). The morphological features supported by molecular markers strongly support the hybrid nature of the collected plants. The results provide evidence that a hybrid between these species really occurs in nature.